Evaluation of characteristics of huizache (Acacia farnesiana (L.) Willd.) fruit for potential use in leather tanning or animal feeding - Barrientos-Ramírez, Lucía; Vargas-Radillo, J. Jesús; Rodríguez-Rivas, Antonio; Ochoa-Ruíz, Héctor Guillermo; Navarro-Arzate, Fernando; Zorrilla, José (Instituto de Ecología, A.C., 2012)
Huizache (Acacia farnesiana (L.) Willd.) is a wild species commonly distributed in Jalisco andother states of Mexico, which may be used as forage. A study was performed on the fruit of huizache(husk and seed) in both, untreated samples and samples with pre-extraction of tannin, for the determinationof chemical proximal analysis (QPA), aminoacid profile, and in situ degradability, in fistulatedpelibuey sheep specimens. Tannins were evaluated using the ALCA method and the Stiasny numbertechnique. QPA analysis showed high protein content in raw seeds of 23,0%, higher than husk content